1998
DOI: 10.1046/j.1440-1843.1998.00069.x
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomographic findings of environmental asbestos‐related malignant pleural mesothelioma

Abstract: Malignant pleural mesothelioma (MPM) is not an infrequent fatal neoplasm. It is endemically present in some regions of Turkey due to its aetiological relationship to exposure to environmental fibrous minerals. The aim of this study was to determine the thorax computed tomographic (CT) features of environmental asbestos-related MPM. In this study, we examined retrospectively the CT scans of 46 untreated patients with pathological diagnosis of environmental asbestos-related MPM among 151 patients with malignant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 1 publication
1
16
0
2
Order By: Relevance
“…The most frequent radiological features of MPM were pleural effusion and pleural thickening or nodularity. To sum up, the demographical, clinical and radiological characteristics in our series were similar to those in literature (Yilmaz et al, 1998;Wang et al, 2004).…”
Section: Discussionsupporting
confidence: 82%
“…The most frequent radiological features of MPM were pleural effusion and pleural thickening or nodularity. To sum up, the demographical, clinical and radiological characteristics in our series were similar to those in literature (Yilmaz et al, 1998;Wang et al, 2004).…”
Section: Discussionsupporting
confidence: 82%
“…More recently, Yılmaz et al [3]have documented thorax CT findings of environmental asbestos-related pleural mesothelioma in patients from various provinces of Turkey, and they suggested that CT is a useful tool to investigate these pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been reported that environmental asbestos exposure is common among the inhabitants of various districts of Turkey [1, 2, 3]. Yazıcıoğlu et al [1]have demonstrated that the prevalence of pleural plaques caused by environmental asbestos exposure is high among the residents of a number of towns surrounding Diyarbakır, a province in the southeast of Turkey.…”
Section: Introductionmentioning
confidence: 99%
“…The disease is one of the major health problems in Turkey [3]. This is due to the many asbestos deposits which exist in some rural parts of central and eastern Anatolia [3, 4, 5]. The people living in the southeast of Turkey (ST) were also reported to have a high incidence of MPM due to environmental asbestos exposure [6, 7].…”
Section: Introductionmentioning
confidence: 99%